Evaluasi Efisiensi Sektor Ekonomi Kreatif pada Wirausaha Muda di Sekolah Tinggi Ilmu Ekonomi - Anggraita Primatami; Yuridistya Primadhita (JMK (Jurnal Manajemen dan Kewirausahaan), 2021)
The creative economy is an economic sector that results from the development of creativity and ideas. Young entrepreneurs contribute to the improvement of the creative economy sector because they are considered easier to adapt technology, respond to market changes, and think creatively and innovatively. This study aims to evaluate the efficiency of the creative economy sector in entrepreneur students of the College of Economics (STIE). This study used the primary data of 50 entrepreneur students. The research was conducted using the Data Envelopment Analysis (DEA) method by analyzing the input to the output factors. The results showed that 7 out of 50 businesses run by STIE students reached 100% efficiency in January and February. Meanwhile, in March there were 9 businesses that achieved 100% efficiency. As many as 41 businesses have never reached 100% efficiency during January to March 2020. Efficiency improvements for inefficient businesses are carried out by referring to businesses that have been efficient by reducing production costs which include reducing the total cost of labor or raw materials.